Citric acid treatment directly on anaerobic digestor sludge alleviates the inhibitory effect of in-situ generated humic acids by their deconstruction and redistribution. (15th April 2023) - Tang, Yanfei; Sun, Jing; Dong, Bin; Dai, Xiaohu
Highlights: CA treatment directly on the sludge in anaerobic digestion boosted methane production. HA deconstruction and redistribution enhance sludge solubilization and hydrolysis. CA treatment at low dosage can release HA surfactants and proteins e.g. hydrolases. A smart mutex-switch CA treatment strategy was proposed for practical application. Abstract: Humic acids were known to inhibit sewage sludge anaerobic digestion (AD) and many studies have been investigated to deal with the inhibitory effect of humic acids (HA) in raw sludge feeding the digestor. However, HA could also be in-situ produced during the sludge AD process with a significant amount, but the relieving of the inhibitory effect posed by the in-situ produced HA has been historically ignored. Thus, this study attempted to use citric acid (CA), an easily biodegradable polyatomic acid, to directly treat sludge in the anaerobic digestor instead of the feeding sludge, for alleviating inhibition caused by the in-situ produced HA. Results showed that methane production of AD batches with CA pretreatment at 0.06∼0.10 g/g TS on digestor sludge were effectively enhanced, with the highest production being 2.89 times of that observed in control AD without CA treatment and 2.08 times of that achieved by contrast AD with CA pretreatment on raw sludge. However, the AD batches with CA treatment at low dosages of 0.02∼0.04 g/g TS had lower methane production, during which sludge solubilization and hydrolysis were enhanced initially associated with released HA surfactant and hydrolytic enzymes; then later inhibited since higher structurally sound HA in SP easily rebind proteinaceous substrates and enzymes again. Whilst CA treatment at 0.06∼0.10 g/g TS could promote sludge solubilization and hydrolysis throughout the sludge AD process. This dosage-dependent effect of CA treatment can be caused by its discriminating impact on HA structure and distribution. At low dosages, complexes of HA-proteins (including hydrolases) can be decrosslinked and transferred to the soluble phase (SP), thus enhancing solubilization and hydrolysis initially. However, the released HA in SP could rebind more organics and hydrolases during AD, resulting in augmented inhibition. While the dosage increased, HA were drastically deconstructed with aromatic cores in SP migrating to extracellular polymeric substances, preventing binding effects on organics and hydrolases. Accordingly, a smart mutex-switch operational strategy of CA treatment was proposed. The results suggested, to alleviate the inhibitory effect of HA on sludge AD, more attention should be given to HA produced and accumulated in AD rather than raw sludge so that the CA treatment directly on sludge in the digestor can be a promising method. Graphical abstract: Image, graphical abstract